PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS VB SDN 61 HARAPAN BARU KECAMATAN MANDAU - Temu Kasih; Zariul Antosa; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was conducted because of the result of learning outcomes sains study class IVB SD Negeri 61 Harapan Baru Kecamatan Mandau. From 22 students who achieve KKM just 8 students (37%) while student who did’nt complete 14 students (63%) with an average of 58. The purpose of this research to improve learning outcomes IPA class IVB SDN 61 Harapan Baru with the application of learning models CTL. The results obtained by the average value of 58 basic score increased in the first cycle of 26,69% to 73,64 . In the scond cycle the average value of students also increased by 42,04% to 82,40. On the basis of completeness score IPA student learning outcomes is only 58% (not finished). After the professor of applied learning model Contextual Teaching and Learning (CTL) in the first cycle classical completeness increased to 63% (not finished) ,the second cycle classical completeness obtained are increased to increase to 82% activities of teachers at the first meeting of 62% with enough categories. The second meeting increased to 75% in both categories . In the second cycle increased to 81% with the category very well. At a meeting of the second meeting of the second cycle, the activities of teachers increased to 95% with the category very well. Activities of studentsin the first cycle of thr first meeting activity students acquire a percentage of 56% in both categories. The second meeting of the first cycle to 75% in both categories. At the first meeting of the scond cycle of students activity increased to 82% with the categoryvery well,and at the second meeting of the second cycle increased again to 95% with the category very well.Key Words : Contextual Teaching end Learning, learning outcomes IPA